Solution:
Given the equation:
![4x^2-10x-36=0\text{ ---- equation 1}](https://img.qammunity.org/2023/formulas/mathematics/college/r5tk1jiyqrny5lmct574t88mlf2t8mna3s.png)
To solve using the quadratic formula, we have the solution of the quadratic equation:
![y=ax^2+bx+c\text{ ---- equation 2}](https://img.qammunity.org/2023/formulas/mathematics/college/tse59ymlwdwank2c97d8mhtkbm2br3y8az.png)
to be
![x=(-b\pm√(b^2-4ac))/(2a)\text{ ----- equation 3}](https://img.qammunity.org/2023/formulas/mathematics/college/o77rkbsp47g2y1ay5ph52q5lgifsrwugok.png)
Comparing equations 1 and 2, we have
![\begin{gathered} a=4 \\ b=-10 \\ c=-36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sflphr33ii1lv6zw1i9f9so5ktpphssaj6.png)
By substituting these values into equation 3, we have
![\begin{gathered} x=(-(-10)\pm√((-10)^2-4(4*-36)))/(2(4)) \\ =(10\pm√(676))/(8) \\ =(10\pm26)/(8) \\ \Rightarrow x=(10+26)/(8)=(9)/(2) \\ or \\ \Rightarrow x=(10-26)/(8)=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2gx6dgnfnxvse4elp30x1rm2w2ey4kw0q0.png)
Hence, the solution, using the quadratic formula, is
![x=(9)/(2)\text{ or x=-2}](https://img.qammunity.org/2023/formulas/mathematics/college/vcnlbs7dd7kxwg63jnzqg2bq37bse3qqsn.png)